RANCANG BANGUN SISTEM INFORMASI PERSEDIAAN BARANG BERBASIS WEBSITE - Muhammad Fikri; Bagas Muhammad Husain; Irwan Putra Ndruru; Fikarlin Ndruru; Fasahati Laiya (Jurnal Riset Teknik Komputer, 2025)
The advancement of technology has significantly facilitated various aspects of human life, including business, health, education, and more. One such technological application is the use of computer-based inventory management systems that streamline data management processes, from recording to quick and accurate data retrieval, while also monitoring assets. PT. SAC Nusantara, established in 1971, faces challenges in its Bandar Lampung branch, where inventory management is still done manually, leading to slow data input, frequent errors in stock calculations, and delayed reporting. To address these issues, a computerized inventory management system is needed to improve efficiency, accuracy, and monitoring. This study aims to design, build, and develop a web-based inventory management system to replace the manual processes. The research utilizes the Framework for the Applications of System Thinking (FAST) method, which is flexible and allows for rapid development with user involvement in each stage. The system is designed to automate the recording and reporting process, reduce errors, and improve real-time inventory tracking. The FAST method, along with Data Flow Diagram (DFD) and Entity Relationship Diagram (ERD), will be used to analyze and design the system. The system's functionalities, such as item entry, exit records, and reporting, are evaluated through black-box testing. The expected outcome of this research is a web-based inventory management system that increases the efficiency and effectiveness of inventory management, providing accurate and timely data that will support decision-making processes. The findings indicate that the implementation of this system will significantly improve inventory handling at PT. SAC Nusantara's Bandar Lampung branch.